THE ACCEPTANCE OF MEDICAL RECORD OFFICER TOWARDS MRMIS IN X HOSPITAL MATARAM - Nurul Khatimah Ismatullah; Aris Puji Widodo; Sri Achadi Nugraheni (Universitas Airlangga, 2022)
Background: MRMIS needs to be evaluated to know the actual conditions of implementing the system . One of the evaluations that can be done is user acceptance of MRMIS. Aims: The study aims to determine MRMIS acceptance in X hospital Mataram City based on the variables in the UTAUT model. Methods: This is a quantitative study with a correlational approach. The sample size was 70 medical record officers using total sampling. Data processing used Partial Least Square (PLS) methodd. Results: The test results showed the t-statistic of effort expectancy was 2.507, facilitating conditions 3.787 behavioural intention 4.928, however the performance expectancy, social influence and moderate variables like age and gender variables had t-statistic values below 1.96. Conclusion: The variables of effort expectancy, enabling conditions, and behavioural intentions all have a significant impact on respondent acceptance of MRMIS, whereas the variables of performance expectancy, social influence, and moderate variables of age and gender do not.